CONTEMPORARY CHALLENGES AND PROSPECTS FOR TAKAFUL PRACTICES IN MALAYSIA: AN ANALYSIS OF CURRENT ISSUES - Muhammad Zarunnaim Haji Wahab; Mohamad Hanif Abu Hassan (International Journal of Accounting, Finance and Business, 2023)
This study investigates the current issues faced by takaful operators (TO) in Malaysia. Qualitative research methodology was employed to gather data through in-depth interviews with seven individuals who are actively involved in the industry, policy makers and academicians. Additionally, focus group discussions were conducted with the Cooperative Commission of Malaysia (CCM) to understand the legal aspects of the cooperative approach. The findings reveal several issues faced by TOs, such as injustice in serving the interest of shareholders and participants, second layer of takaful charge in mudarabah model, Shariah issues (wakalah fee, tabbaru’ issue, ownership of return and underwriting surplus) and legal issues related to capital adequacy, deposit insurance, paid-up capital, and other requirements. This paper contributes to the literature by shedding light on the challenges faced by TOs in Malaysia and provides insights for policymakers and industry practitioners to address these issues.